Trickle irrigation design for Malaysian agriculture. - Said, Salim; Mohd. Idris, Noraishah (1988)
Trickle irrigation is becoming very popular in Malaysia today. It is being tried for irrigation of all kind of crops grown on soils of different classes. Being quite expensive, it is most beneficial if used on soils of low quality. Parameter for the design still need to be ascertained and system performance need to be evaluated. A preliminary computer programme on the design of the trickle irrigation system for Malaysia tree crops is presented.